Access Reform for Green Economy: Community-Based Woven Fabric Waste Management in Troso Village - Munawaroh, Lu’lu’il; Mansyur, Mohammad (Jurnal Pertanahan, 2025)
This study examines the integration between access reform in the Agrarian Reform policy and green economy initiatives in Troso Village, Jepara Regency, using woven fabric waste as a productive resource. Troso Village is a center for traditional weaving crafts that produces significant textile waste. In the 2022 Agrarian Reform Access Handling Program, the Jepara Regency Land Office, together with the Cooperatives, SMEs, Manpower, and Transmigration Service, held training on the utilization and recycling of woven fabric waste for 300 Agrarian Reform subjects. This study uses an exploratory descriptive qualitative approach approach with a case study design and thematic analysis techniques. The study results indicate that access reform catalyzes local innovation by encouraging communities to develop creative waste-based products, such as bags, wallets, and household accessories. This activity reduces environmental impacts and improves community welfare through a business model that aligns with the principles of a green economy and a circular economy. This study recommends that this community empowerment model based on waste utilization be applied in other areas as a strategy for transforming the village economy towards sustainable green economy practices that are adaptive to local potential. Penelitian ini mengkaji integrasi antara access reform dalam kebijakan Reforma Agraria dengan inisiatif ekonomi hijau di Desa Troso, Kabupaten Jepara, melalui pemanfaatan limbah kain tenun sebagai sumber daya produktif. Desa Troso merupakan sentra kerajinan tenun tradisional yang menghasilkan limbah tekstil dalam jumlah signifikan. Pada Program Penanganan Akses Reforma Agraria tahun 2022, Kantor Pertanahan Kabupaten Jepara bersama Dinas Koperasi, UMKM, Tenaga Kerja, dan Transmigrasi menyelenggarakan pelatihan pemanfaatan serta daur ulang limbah kain tenun bagi 300 subjek Reforma Agraria. Penelitian ini menggunakan pendekatan kualitatif deskriptif eksploratif dengan desain studi kasus dan teknik analisis tematik. Hasil penelitian menunjukkan bahwa access reform mendorong inovasi lokal dengan menggerakkan masyarakat untuk mengembangkan produk kreatif berbasis limbah, seperti tas, dompet, dan aksesori rumah tangga. Kegiatan ini mampu mengurangi dampak lingkungan sekaligus meningkatkan kesejahteraan masyarakat melalui model bisnis yang selaras dengan prinsip ekonomi hijau dan ekonomi sirkular. Penelitian ini merekomendasikan model pemberdayaan masyarakat berbasis pemanfaatan limbah untuk diterapkan di wilayah lain sebagai strategi transformasi ekonomi desa menuju praktik ekonomi hijau berkelanjutan yang adaptif terhadap potensi lokal.